Peningkatan Kompetensi Guru Dalam Pembelajaran Berbasis Proyek (Project-Based Learning) di Sekolah Dasar - Anggraini Nasution (Educational Journal, 2026)
The implementation of Project-Based Learning (PjBL) is one of the approaches carried by the Merdeka Curriculum to create contextual, creative, and student-centered learning. This model requires teachers to have adequate pedagogical, professional, social, and technological competencies. However, the facts show that many elementary school (SD) teachers still face challenges in understanding, designing, and implementing Project-Based Learning optimally. This study aims to analyze the challenges faced by teachers in implementing Project-Based Learning, as well as exploring various efforts made to improve teacher competence. The study uses a literature study method with descriptive analysis of various sources, including journals, e-proceedings, and bold news. The results of the study show that intensification of training, academic supervision, and strengthening digital literacy contribute significantly to improving teacher competence. In addition, the implementation of Project-Based Learning has been shown to have a positive impact on learning outcomes and 21st-century skills of elementary school students. Therefore, improving teacher competence needs to be used as an example of a sustainable and structured program so that the implementation of Project-Based Learning runs optimally in elementary schools.